Assessment of transportation processes of polyacrylamide in chernozem and saline soil by numerical model. Issue 15 (3rd July 2021) - Zhang, Huibo; Jing, Guolin; Luo, Jian; Tang, Yuening; Yu, Qiming Jimmy; Zheng, Chen; Wang, Mengqi
ABSTRACT: Polyacrylamide (PAM) was studied in two characteristic soils in Daqing City: chernozem and saline soil. 120 mg L −1 of KBr was used as a conservation tracer to estimate diffusion coefficients and pore velocities of chernozem and saline soil by using the breakthrough curves (BTCs) of Br – . Isothermal adsorption equations were coupled with the traditional two-site model to establish the transportation equation of PAM. The results of comparing the simulation curve with the BTCs of PAM at different rates showed that the transportation equation of PAM could simulate the transport process of PAM in soil column accurately. PAM behaved as non-equilibrium adsorption in both soils by calculating the kinetic parameters in this equation. The results of this work not only confirmed the kinetic parameters of PAM in both soils, but also found that there is a good liner relationship between the mass transfer coefficient and pore velocity. The R 2 values of the two linear equations are 0.983 and 0.979. These linear equations provide a good prediction basis for site prediction. In addition, it was found that organic matter is the main influence factor for the adsorption capacity of chernozem causing significantly larger than that of saline soil. GRAPHICAL ABSTRACT: UF0001